Subacute Sclerosing Panencephalitis Presenting with Hemidystonia - Serin, Hepsen Mine; Bilen, Sevcan; Cansu, Ali (Galenos Yayincilik, 2014)
In this paper, we present a case of subacute sclerosing panencephalitis (SSPE) in an 11-year-old boy who presented with hemidystonia. Electroencephalogram (EEG) revealed periodic epileptiform discharges which did not disappear with diazepam induction. His cranial magnetic resonance imaging was normal. SSPE diagnosis was considered and it was confirmed with the identification of measles antibodies in cerebrospinal fluid. SSPE is a progressive disease. Hemidystonia is not an expected presentation of SSPE. We aimed to emphasize that SSPE may present with different clinical findings such as hemidystonia.
Hemidistoni ile Prezente Olan Subakut Sklerozan Panensefalit
Keywords: Subacute sclerosing panencephalitis; hemidystonia; measles